The Local Economic Development through Maggot Cultivation in Klaten, Indonesia, to Support Environmental Sustainability - Muhammad Rofiud Mutaal (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This article discusses local economic development through maggot cultivation by taking a case study in one of the villages in Klaten Regency, Central Java. Environmental problems related to waste have also become a concern for the government to solve. One way that can be used is maggot bioconversion. This research aims to analyze how the local economic development process includes locality, business, monetary base, employment resources, and community resources for maggot cultivation carried out by Gempol Village while still positively impacting environmental problems. This research will also provide an overview of the challenges, opportunities, and policy implications of local economic development through maggot cultivation. Karanganom Village was chosen as the research locus because of its success in cultivating maggots by involving village communities as a form of local economic development that can provide economic benefits. The method used in this research uses a qualitative research model with a descriptive empirical approach. The data collection technique used was through interviews, and the informant selection technique used was purposive sampling. Local economic development in Gempol Village was analyzed using the Local Economic Development theory, namely locality, business and the economic base, Employment resources, and community resources. The results of this article are that local economic development by cultivating maggots in Gempol Village, Karanganom District, Klaten Regency has had a positive impact on the community's economy, such as job creation, increased income and diversification of sources of income, and increased skills and education. Additionally, maggot cultivation in Gempol Village positively impacts the environment by helping decompose waste within a few days and reducing waste disposed of in landfills. This research contributes significantly to understanding how maggot cultivation can effectively aid local economic development and environmental conservation.